Workshop on Article Writing in Reputable International Journals For Master of Science Education Students - Aris Doyan; Susilawati Susilawati; Saprizal Hadi Saputra; Syamsul Hakim (Pascasarjana Universitas Mataram, 2022)
The workshop on writing scientific articles in reputable international journals was attended by 20 participants. This activity is carried out to overcome the problems of students who have difficulty in choosing reputable international journals. The implementation of the workshop was carried out by the method of discussion and demonstration. Discussions related to the general structure of writing articles in reputable international journals and demonstrations to find out the destination journals of reputable publications through Scimago, published by Elsevier, and published by Springer. This workshop activity succeeded in helping students because 80% of the students participating in the workshop could write articles well and choose reputable international journals.